2013
DOI: 10.1371/journal.pgen.1003254
|View full text |Cite|
|
Sign up to set email alerts
|

An Evolutionarily Conserved Synthetic Lethal Interaction Network Identifies FEN1 as a Broad-Spectrum Target for Anticancer Therapeutic Development

Abstract: Harnessing genetic differences between cancerous and noncancerous cells offers a strategy for the development of new therapies. Extrapolating from yeast genetic interaction data, we used cultured human cells and siRNA to construct and evaluate a synthetic lethal interaction network comprised of chromosome instability (CIN) genes that are frequently mutated in colorectal cancer. A small number of genes in this network were found to have synthetic lethal interactions with a large number of cancer CIN genes; thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 66 publications
5
63
1
1
Order By: Relevance
“…High expression of FEN1 is associated with clinicopathological significance and poor survival (26), suggesting that FEN1 has an important role in the development of breast cancer. It has previously been demonstrated that anticancer therapies are able to induce FEN1 expression (5), and inhibition of FEN1 combined with DNA injury agents results in increased inhibition of proliferation via endogenous DNA damage (12,(27)(28)(29). In the present study, it was demonstrated that trastuzumab promoted the activation of HER2 and AKT, and concurrently upregulated FEN1 protein expression in BT474 breast cancer cells.…”
Section: Discussionsupporting
confidence: 59%
“…High expression of FEN1 is associated with clinicopathological significance and poor survival (26), suggesting that FEN1 has an important role in the development of breast cancer. It has previously been demonstrated that anticancer therapies are able to induce FEN1 expression (5), and inhibition of FEN1 combined with DNA injury agents results in increased inhibition of proliferation via endogenous DNA damage (12,(27)(28)(29). In the present study, it was demonstrated that trastuzumab promoted the activation of HER2 and AKT, and concurrently upregulated FEN1 protein expression in BT474 breast cancer cells.…”
Section: Discussionsupporting
confidence: 59%
“…Several interesting interactions emerged, including SLIs between the FEN1 flap endonuclease and genes whose homologs are frequently mutated in colorectal cancer, such as MRE11A and CDC4. Interestingly, small molecule inhibition of FEN1 in cancer cells with mutated MRE11A or CDC4 recapitulated the SLI phenotype identified in yeast (van Pel et al, 2013a). This result emphasizes the importance of model organisms in the identification of clinically relevant synthetic lethal interactions in human tumors.…”
Section: Faithful Lovers -Polymerases and Their Partnersmentioning
confidence: 59%
“…99 A study in colorectal cancer cell lines revealed that FEN1 inhibition by a number of small molecules had a synthetically lethal effect in cells deficient in the ubiquitin ligase CDC4. 115 Interestingly, in a recent study, curcumin, the active ingredient in turmeric, has been shown to restrict cell proliferation in breast cancer cell lines through inhibition of FEN1 activity. 116 It was shown that curcumin upregulates expression of the transcription factor NF-E2-related factor 2 (nrf2).…”
Section: Fen1 Inhibitorsmentioning
confidence: 99%